The Challenge of The Integrated Character Education Paradigm with 21st-Century Skills During The Covid-19 Pandemic - Susanto, Susanto; Ritonga, Apri Wardana; Desrani, Ayu (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study explores a new paradigm of character education with 21st-century skills through online learning during the Covid-19 pandemic in Indonesia. The researcher adopted a qualitative approach with the library research method. Research data were collected from primary and secondary sources such as books, proceedings, and journals. The collected data is then analyzed using descriptive content analysis by selecting, comparing, and presenting the data findings deductively. This research shows that students with 21st-century character and skills will become individuals who can take opportunities and face global development challenges. The findings of this study describe that online learning is an excellent opportunity for teachers to instill technology-based character values. An in-depth study is needed to complete this study by discussing the role of parents and teachers in instilling character education during online learning.